Role of Brand Image and Switching Cost on Customer Satisfaction-Loyalty Dyadic in the Mid-Market Hotel Sector - Jana, Abhisek; Chandra, Bibhas (Indian Journal of Marketing, 2016)
The study attempts to analyze the relationship between customer satisfaction and progressive phases of loyalty in mid-market hotel precinct. It succinctly intended to gauge the direct effects of brand image and switching cost on progressive phases of loyalty and moderating effects of brand image and switching cost on the satisfaction-loyalty dyadic. The outcome of the study revealed that customer satisfaction has a strong positive impact on cognitive loyalty, but unexpectedly not on affective, conative, and action loyalty in the hotel sectors of midmarket. Further, brand image has a direct and significant effect on progressive levels of loyalty. It moderates the link between customer satisfaction and affective loyalty; and customer satisfaction and action loyalty. The direct effect of switching cost on cognitive and affective loyalty is insignificant, but on conative and action loyalty is positive and significant. Further investigation of the moderating effects of switching cost shows that it strengthens the negative relationship between customer satisfaction and conative loyalty; customer satisfaction and action loyalty. But it dampens the negative relationship between customer satisfaction and affective loyalty. The results would provide necessary inputs and managerial insights to develop marketing strategies through careful introspection of their present positions in the loyalty-satisfaction matrix. This research is premised on questioning the status quo regarding the customer satisfaction-loyalty link and factually argued that customer satisfaction is necessary, but is not a sufficient condition to forge loyalty. Meagre studies have attempted to integrate switching cost and brand image with customer satisfaction and loyalty relationship. This research gap is further evident due to sporadic research on moderating effects of switching cost and brand image directly and in interactions with satisfaction on progressive levels of loyalty. This study provides new insights and enlightens some phenomenon explaining customer satisfaction-loyalty dyadic interactions in emerging mid-market hotel segment.